Biogenesis of Silver Nanoparticles and Its Multifunctional Anti-Corrosion and Anticancer Studies - Hublikar, Leena V; Ganachari, Sharanabasava V; Raghavendra, Narasimha; Banapurmath, Nagaraj R; Patil, Veerabhadragouda B.; Yunus Khan, T. M; Badruddin, Irfan Anjum (MDPI, 2021)
In the present research, silver nanoparticles were synthesized using ground nutshell and characterized using UV-visible, FTIR and PXRD. The SEM and HR-TEM aided in confirming the nano size, surface morphology and phase purity of the AgNPs. The quantum chemical, electrochemical, and structural studies were carried out to understand electrochemical properties. In addition, biological study such as anti-cancerous activity was carried out, and IC-50 values 80.25 mu g/mL for A549 lung cancer cell lines. The effective electrochemical anti-corrosion activities were also studied. The majority constituents of ground nutshell are flavonoids, in a small quantity of alkaloids and phenolic acids, which provide more stability to synthesize silver nanoparticles and avoid agglomeration. These functional moieties enhance the unique properties in the field, as in drug delivery systems, magnetic applications, and metallic, semi-conducting core-shell nanoparticles.
Biogeneze nanočástic stříbra a jejich multifunkčnost antikorozní a protinádorové studie
Keywords: ground nutshell extract; silver nanoparticles; high-resolution transmission electron microscopy; corrosion inhibition; Tafel plots; anti-cancerous activity; extrakt z mletých skořápek ořechů; nanočástice stříbra; transmisní elektronová mikroskopie s vysokým rozlišením; inhibice koroze; Tafelovy grafy; protirakovinná aktivita